20 A comparison of two iFR methods to predict FFR (fractional flow reserve) - the blackpool coronary iFR study (BCIS). (24th April 2016) - Galasko, Gavin
Abstract : Background: The iFR (instantaneous free-wave ratio) is a new adenosine-independent measure of ischaemia possibly equivalent to FFR. 2 cut-offs have been mooted: A) iFR ≤0.89 abnormal and B) iFR <0.86 abnormal, iFR >0.93 normal and iFR 0.86–0.93 a grey-zone where FFR should be measured (hybrid approach). No study has prospectively assessed A vs B. Methods: Consecutive patients undergoing FFR had iFR measured first with A vs B compared in predicting FFR. Results: 55 consecutive patients were assessed: 34 men, mean age 63. 105 coronary arteries were assessed: mean FFR 0.84; 36 (34%) FFR ≤0.8; mean iFR 0.92; 34 (32%) iFR ≤0.89; 12 (11%) had iFR <0.86, 50 (48%) iFR 0.86–0.93 and 43 (41%) iFR >0.93. The correlation between iFR and FFR gave R2 0.64. The overall agreement between iFR and FFR was 79% using method A vs 98% using the hybrid/grey-zone approach. The sensitivity, specificity, PPV and NPV were: 71% vs 100%; 83% vs 97%; 67% vs 94% and 86% vs 100%, respectively, with the hybrid approach superior for each value. Of the 50 grey zone cases, 22 (44%) had FFR ≤0.8 with method A only 60% accurate in predicting FFR. Outside the grey zone, method A was 96% accurate in predicting FFR. iFR was highly reproducible with 95% limits of agreement +0.01–0.015. Conclusion: The iFR is reproducible with modest correlation to FFR. Outside the grey zone, iFR <0.86 as abnormal and >0.93 as normal accurately predict FFR. Within the grey zone iFR 0.86–0.93 adenosine should be given and FFR measured. Using this approach 52% of cases would not require adenosine, with 98% accuracy.